PENGARUH KOMBINASI KOMPOS JERAMI PADI DAN BIOCHAR SEKAM PADI TERHADAP KETERSEDIAAN HARA NPK DAN PERTUMBUHAN TERUNG UNGU PADA TANAH ALUVIAL - Melianti, Melianti; Hayati, Rita; Alhaddad, Abdul Mujib (Fakultas Pertanian, Universitas Janabadra, 2024)
Cultivation of purple eggplant plants in alluvial soils has several obstacles, one of which is the lack of macro and micro nutrients, so to overcome this it is necessary to give a combination of rice straw compost and rice husk biochar to increase the availability of nutrients N, P, K and the growth of purple eggplant plants on alluvial soils. This study aims to determine the effect of a combination of rice straw compost on the availability of nutrients N, P, K and the growth of purple eggplant plants (Solanum melongena L.) in alluvial soil. This research took place from May - September 2023, conducted at the experimental land of the Faculty of Agriculture, Tanjungpura University, Pontianak City, West Kalimantan. This study used a completely randomized design (CRD) consisting of 1 factor with 6 treatments, namely: P0 = no treatment; P1 = compost 244 g/polybag; P2 = biochar 217 g/polybag; P3 = compost 183 g/polybag + biochar 54 g/polybag; P4 = compost 122 g/polybag + biochar 108 g/polybag; P5 = compost 61 g/polybag + biochar 163 g/polybag. Each treatment was repeated 4 times so there were 24 polybags. The results showed that the best dose of the combination of rice straw compost and rice husk biochar was found in the 30 ton/ha treatment (P1) which could increase N-total by 73.23%, plant height by 28.18% and stem diameter by 13.75%Key words: alluvial soil; purple eggplant; rice straw compost; rice husk biocharINTISARI Budidaya tanaman terung ungu di tanah aluvial memiliki beberapa kendala, satu diantaranya yaitu kekurangan unsur hara makro dan mikro, sehingga untuk mengatasi hal tersebut diperlukan pemberian kombinasi kompos jerami padi dan biochar sekam padi untuk meningkatkan ketersediaan hara NPK serta pertumbuhan tanaman terung ungu pada tanah aluvial. Penelitian ini bertujuan untuk mengetahui pengaruh kombinasi kompos jerami padi terhadap ketersediaan hara NPK dan pertumbuhan tanaman terung ungu (Solanum melongena L.) di tanah aluvial. Penelitian ini berlangsung sejak Mei – September 2023, dilaksanakan di lahan percobaan Fakultas Pertanian Universitas Tanjungpura Kota Pontianak, Kalimantan Barat. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) terdiri 1 faktor dengan 6 perlakuan, yaitu: P0 = tanpa perlakuan; P1 = kompos 244 g/polybag; P2 = biochar 217 g/polybag; P3 = kompos 183 g/polybag + biochar 54 g/polybag; P4 = kompos 122 g/polybag + biochar 108 g/polybag; P5 = kompos 61 g/polybag + biochar 163 g/polybag. Setiap perlakuan diulang sebanyak 4 kali sehingga terdapat 24 polybag. Hasil penelitian menunjukkan dosis terbaik kombinasi kompos jerami padi dan biochar sekam padi, yaitu terdapat pada perlakuan 30 ton/ha (P1) dapat meningkatkan N-Total 73.23%, tinggi tanaman 28.18% dan diameter batang sebesar 13.75%.Kata kunci: biochar sekam padi; kompos jerami padi; tanah aluvial; terung ungu